Pengaruh Lingkungan Kerja Terhadap Motivasi Karyawan Bagian Produksi di PT. Permata Borneo Lestari Kabupaten Mempawah - Dian Puspita Sari; Devi Yasmin; Fenni Supriadi (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of the work environment on employee motivation at PT. Permata Borneo Lestari Mempawah Regency. The number of samples used in this study was 70 people.The data analysis techniques in this study are Simple Linear Regression Analysis, Correlation Coefficient Analysis (r), Determination Coefficient Analysis (R2), Feasibility Test Regression Model (Test F). the results of this study note that the regression equation Y = 2,983 + 0,387X. The value of the Correlation Coefficient (r) is 0,466, which means that the relationship between the work environment and employee motivation at PT. Permata Borneo Lestari Mempawah Regency is medium. The value of the coefficient of determination (R2) is 0,217. it means that the contribution of the variable Work Environment in influencing the ups and downs of Work Motivation of employees at PT. Permata Borneo Lestari Mempawah Regency is 21,7% and the remaining 78,3% is influenced by other variables not examined in this study. The calculated F value is 18,889. This is higher than f table which is worth 3,98. it means that the linear regression model can be used to predict the value of Employee A motivation that is influenced by the Work Environment at PT. Permata Borneo Lestari Mempawah Regency.